VAIC Method and Islamic Social Reporting: Tools for Measuring Firm Value - Wahyu Setyawan (ITB AAS Indonesia Surakarta, 2025)
This study examines the influence of Value added intellectual coefficient (VAIC) and Islamic Social Reporting (ISR) on firm value within Islamic contexts, employing a quantitative approach with data from 40 companies listed on the Indonesian stock exchange from 2019 to 2022. The results reveal a significant positive relationship between VAIC and firm value, indicating that efficient management of intellectual capital enhances market valuation. Conversely, ISR demonstrates a significant negative impact on firm value, suggesting that the costs associated with ethical and social compliance may outweigh short-term financial benefits. The study contributes to the literature by integrating VAIC and ISR into a dual performance measurement framework, offering insights for businesses seeking to balance financial and ethical objectives. However, the research has limitations, including a narrow sample limited to Indonesian companies and a short observation period, which may affect the generalizability of the findings. Future studies could expand the geographical scope and incorporate longitudinal data to validate these results across diverse Islamic business environments.